1999
DOI: 10.1042/bj3440031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Oryza sativa 16·9 kDa heat shock protein

Abstract: A rice class I low-molecular-mass heat shock protein (LMM HSP) Oshsp 16.9 was overexpressed in Escherichia coli. Oligomerized complexes of Oshsp16.9 were harvested and electron microscopic observations of purified complexes revealed globular structures of 10-20 nm in diameter (with majority of 15-18 nm) and calculated to comprise approx. 12 monomers per complex. In comparison, complexes from native rice class I LMM HSPs were observed as larger ellipsoid- or globular-like random aggregated hetero-oligomers. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Increased abundance of HSPs indicates their potential role in processing the elevated levels of B- and C-hordeins, which together represent >95% of total prolamin. Increased abundance of HSPs was reported earlier in rice, wheat, and a high-lysine maize mutant, where the synthesis of storage proteins is common.…”
Section: Resultssupporting
confidence: 71%
“…Increased abundance of HSPs indicates their potential role in processing the elevated levels of B- and C-hordeins, which together represent >95% of total prolamin. Increased abundance of HSPs was reported earlier in rice, wheat, and a high-lysine maize mutant, where the synthesis of storage proteins is common.…”
Section: Resultssupporting
confidence: 71%
“…It was reported that β2 strand was involved in structure dimerisation of HSP16.5 and HSP 16.9. The β7 strand was found to play crucial role in the dimer formation in the human sHSP proteins (Young et al, 1999) and presence of conserved arginine residue significantly contributes to dimerisation and found to be associated with human pathologies (Carugo and Pongor, 2001). The solved crystal structure of HSP16.5 and HSP16.9 from M. jannaschii and wheat respectively, revealed that swapping of β6 strand leads to protein dimer formation and oligomerisation (van Montfort et al, 2001b).…”
Section: Structure and Sequences Analysismentioning
confidence: 99%